UndercoverEisAgenten - The Arctic Permafrost Citizen Science Project - Mueller, Marlin M.; Thiel, Christian; Klan, Friederike; Lenz, Josefine; Kaiser, Soraya; Langer, Moritz; Lantuit, Hugues; Marx, Sabrina; Fritz, Oliver; Zipf, Alexader (2022)
People in the Arctic have been experiencing severe changes to their environments for several decades. In particular the thawing of permafrost affects the livelihoods of indigenous people and has far-reaching ecological impacts including the additional release of greenhouse gases. By fusing local knowledge on landscape changes in Northwest Canada and remote sensing, we seek to better understand and monitor land surface changes attributable to permafrost thaw. The goal is to investigate permafrost thaw impacts through the acquisition and analysis of imagery from Unmanned Aerial Vehicles (UAVs) and satellites together with young Citizen Scientists from schools in Northwest Canada and Germany. For this, we utilize DJI Mini 2 drones in combination with the Litchi for DJI mobile application as the controller software. This combination allows for the easy creation of flight mission with standardized parameters to enable reproducible results. Permafrost landscapes often feature striking polygonal surface structures which change dynamically when thawing processes are in progress. The polygonal landscape structures extend over different spatial scales and can be used to determine the severity of permafrost thaw. While very high-resolution UAV imagery provides detailed insights into the small-scale thermo-hydrological and geomorphological processes, local knowledge and experience is required to identify relevant sites and to set the environmental changes into temporal, cultural, societal, and economic context. These data and background information are urgently needed to improve our prediction on the impacts of permafrost thaw. To this end, school classes in Germany and the Canadian Arctic will collaborate on the analysis of high-resolution remote sensing data. The students will use a mobile application to map striking structures and changes in the land surface on satellites and UAV images. Utilizing feedback from co-creative workshops with German teachers, concepts are being developed to introduce the different topics of ...